Abscess in Adenomyosis Mimicking a Malignancy in a 54-Year-Old Woman - Rezzan Erguvan; Mehmet M. Meydanli; Alpay Alkan; Mehmet N. Edali; Hasan Gokce; Ayşe Kafkasli (Hindawi Limited, 2003)
Background: Although there are a few reports describing abscess formation in endometriotic foci no report of abscess formation arising de novo within adenomyosis appears in the literature. Preoperative diagnosis of adenomyosis is frequently difficult because of non-specific signs and symptoms. Synchronous pelvic pathologies such as leiomyoma, endometrial polyp, endometrial hyperplasia, as well as endometrial cancer may cause differential diagnostic problems.